Molecular interactions between green tea catechins and cheese fat studied by solid-state nuclear magnetic resonance spectroscopy. (15th January 2017) - Rashidinejad, Ali; Birch, Edward J.; Hindmarsh, Jason; Everett, David W.
Highlights: Significant change in the molecular mobility in cheese is caused by tea catechins. Hydrophobic and/or cation–π associations occur between tea catechins and cheese fat. Solid-state WISE NMR revealed interactions between catechins and cheese components. Catechins alter the molecular mobility of a 13 C peak at 16 ppm in cheese. Abstract: Molecular integrations between green tea catechins and milk fat globules in a cheese matrix were investigated using solid-state magic angle spinning nuclear magnetic resonance spectroscopy. Full-fat cheeses were manufactured containing free catechin or free green tea extract (GTE), and liposomal encapsulated catechin or liposomal encapsulated GTE. Molecular mobility of the carbon species in the cheeses was measured by a wide-line separation technique. The 1 H evolution frequency profile of the 13 C peak at 16 ppm obtained for the control cheese and cheeses containing encapsulated polyphenols (catechin or GTE) were similar, however, the spectrum was narrower for cheeses containing free polyphenols. Differences in spectral width indicates changes in the molecular mobility of –-CH3 – or –C–C–PO4 – species through hydrophobic and/or cation–π associations between green tea catechins and cheese fat components. However, the similar spectral profile suggests that encapsulation protects cheese fat from interaction with catechins.